The Role of Interleukin-1Beta and Other Potential Genetic Markers as Indicators of Gastric Cancer Risk - Esther Troost; Georgina L Hold; Malcolm G Smith; Wong-Ho Chow; Charles S Rbkin; Kenneth EL McColl; Emad M El-Omar (Canadian Journal of Gastroenterology)
Helicobacter pylori infects half of the world’s population, and is associated with asymptomatic gastritis and also with more serious conditions such as peptic ulcer disease and gastric carcinoma. The clinical outcome is largely dependent on the severity and distribution of the H pylori-induced gastritis, but the pathogenesis remains poorly understood. Bacterial virulence factors and environmental influences contribute to the pathogenesis, but do not explain the divergent outcomes. There is emerging evidence that host genetic factors play a key role in determining the clinical outcome of H pylori infection. In particular, proinflammatory genotypes of the interleukin-1 beta (IL-1β) gene are associated with an increased risk of gastric cancer and its precursors. The effects are most likely mediated through the induction of hypochlorhydria and severe corpus gastritis with the subsequent development of gastric atrophy. The roles of IL-1β and other host genetic factors in the pathogenesis of H pylori related cancer are discussed in this article.